Long noncoding RNA nuclear enriched abundant transcript 1 promotes the proliferation and migration of Schwann cells by regulating the miR‐34a/Satb1 axis. Issue 9 (12th February 2019) - Liu, Xiangyu; Yu, Xueyuan; He, Youcheng; Wang, Lu
Abstract: The proliferation and migration of Schwann cells contribute to axonal outgrowth and functional recovery after peripheral nerve injury. Studies have found that long noncoding RNAs (lncRNAs) were abnormally expressed after peripheral nerve injury and they played vital roles in peripheral nerve regeneration. LncRNA nuclear enriched abundant transcript 1 (NEAT1) was increased in the cerebral cortex surrounding the injury site of mice after traumatic brain injury, and it promoted the functional recovery in mice. However, its role and mechanism in peripheral nerve injury remain unknown. The expression of NEAT1, miR‐34a, and Special AT‐rich sequence‐binding protein‐1 (Satb1) was detected in the sciatic nerve of mice after sciatic nerve crush at 0, 1, 4 and 7 days. The effects of NEAT1 on the proliferation and migration of Schwann cells were detected by 5‐Ethynyl‐20‐deoxyuridine (Edu) and transwell by gain‐ and loss‐of‐functions. The mechanism was focused on the miR‐34a/Satb1 pathway. In addition, the effect of NEAT1 in Schwann cells on axon outgrowth of dorsal root ganglion neurons was further investigated. We found that the NEAT1 and Satb1 expression was increased, whereas miR‐34a was reduced, in injured sciatic nerve at different time points. Overexpression of NEAT1 promoted, whereas knockdown of NEAT1 suppressed the proliferation and migration of Schwann cells. NEAT1 functioned as a competing endogenous RNA to regulate the Satb1 expression via sponging miR‐34a. NEAT1 enhanced the axon outgrowth of dorsal root ganglion neurons via regulating the miR‐34a and Satb1 expression. In conclusion, NEAT1 promotes the proliferation and migration of Schwann cell via miR‐34a/Satb1, which may provide a new approach to peripheral nerve regeneration. Abstract : We found nuclear sequence‐binding protein‐1 (NEAT1) and sequence‐binding protein‐1 (Satb1) expression was increased, whereas miR‐34a was reduced, in injured sciatic nerve at different time points. NEAT1 promotes the proliferation and migration of Schwann cell via miR‐34a/Satb1, which may provide a new approach to peripheral nerve regeneration.